Negotiation in Decentralization Case Study of China's Carbon Trading in the Power Sector - Yang, Ming.; Yang, Fan.; SpringerLink (Online service) (London : Springer London, 2012)
The Chinese government set a target to reduce China$1 (Bs carbon intensity by 40%-45% in 2020 at its 2005 level. To achieve this target, the government has allocated targets to provinces, cities, and large enterprises, and selected five pilot provinces and eight cities for CO2 emission trading. Such emission trading process will involve decentralization, optimization, and negotiation. The prime objective of this book is to perform academic research on simulating the negotiation process. Through this research, a methodological framework and its implementation are set up to analyze, model and facilitate the process of negotiation among central government and individual energy producers under environmental, economical and social constraints. Negotiation in Decentralization: Case Study of China's Carbon Trading in the Power Sector discusses research carried out on negotiation issues in China regarding Chinese power sector reform over the past 30 years. Results show that conflicts exist between power groups and the national government, and that the most current negotiation topics in China's power industry are demand and supply management, capital investment, energy prices, and CO2 emission mitigations. Negotiation in Decentralization: Case Study of China's Carbon Trading in the Power Sector is written for government policy makers, energy and environment industry investors, energy program/project managers, environment conservation specialists, university professors, researchers, and graduate students. It aims to provide a methodology and a tool that can resolve difficult negotiation issues and change a loss-loss situation to a win-win situation for key players in a decentralized system, including government policymakers, energy producers, and environment conservationists.s
Executive Summary -- Chapter 1 Introduction -- Chapter 2 Research Background and Review -- Chapter 3 Negotiation Issues in China's Power Industry -- Chapter 4 -- Methodological Framework -- Chapter 5 Case Studies -- Chapter 6 Conclusions and Implications.
Keywords: Engineering; Engineering economy; Environmental economics; Engineering; Energy Economics; Energy Policy, Economics and Management; Environmental Economics